2012
DOI: 10.1177/1082013211433069
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of Cuttlefish (Sepia pharaonis) fillets stored in dry and wet ice

Abstract: Microbiological quality of cuttlefish (Sepia pharaonis) fillets stored in three different ice conditions was studied. Fillets stored in wet ice at a ratio of 1:1 (package III) were sensorially acceptable for only 18 h, while that stored in dry ice at 1:1 (package I) and combination of dry ice and wet ice at 1:0.2:0.5 (package II) were in acceptable condition up to 24 h without re-icing and thus there was an extension of shelf life by about 33%. Total bacterial load was 7 log10 cfu/g at the end of the storage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…Additionally, a decrease in the counts and delay in growth of psychrophilic bacteria could be due to cold shock during storage. Results of this study were in agreement with those of reported by (Jeyasekaran et al, 2011) that investigated the microbiological quality of cuttlefish (Sephia pharaonis) fillets stored under chilled conditions.…”
Section: Resultssupporting
confidence: 92%
“…Additionally, a decrease in the counts and delay in growth of psychrophilic bacteria could be due to cold shock during storage. Results of this study were in agreement with those of reported by (Jeyasekaran et al, 2011) that investigated the microbiological quality of cuttlefish (Sephia pharaonis) fillets stored under chilled conditions.…”
Section: Resultssupporting
confidence: 92%
“…As a result of their bad habits the change in the external appearance of cuttlefish, specially related to a decrease in the skin into a pale dark brownish color and loss of brightness indicating a loss in initial quality of cuttlefish. There are only few studies on cuttlefish quality assessment, most of them are related to determining the chemical, microbiological and sensory changes of the whole cuttlefish during iced storage (Ganesan et al, 2005;Vaz-Pires et al, 2008;Sykes et al, 2009;Tantasuttikul et al, 2011;Jeyasekaran et al, 2012).Quality assessment of cuttlefish is determined using sensory, chemical and microbiological analysis. Sensory analysis is commonly considered as the most important method for freshness evaluation in the fish research (Martinsdóttir et al, 1987).…”
Section: Introductionmentioning
confidence: 99%